La América española a través de "Relaciones" de Cabrera de Córdoba (1599-1614) - Viforcos Marinas, María Isabel (Estudios humanísticos. Geografía, historia y arte, 1994)
In this artide we have tried to give a general view about the news referring to Hispano-American atmosphere, collected by Luis Cabrera de Córdoba in 'Relations of the events happened at the Court of Spain from 1599 to 1614' and from them to be able to approach his particular idea of the New World as the origin of Spanisch Monarchy.